Synthesis of O‐Alkyl Alkylphosphonates via Hydrazine Mediated Partial Dealkylation of Phosphonate Diesters. Issue 1 (3rd January 2018) - Pardasani, Deepak; Purohit, Ajay; Kumar, Ajeet; Tak, Vijay; Goud D, Raghavender; Gupta, Arvind K.; Dubey, Devendra K.
Abstract: Simple and straightforward method for the partial dealkylation of phosphonate esters is reported for the preparation of alkyl alkylphosphonates. Hydrazine hydrate is used under solvent free conditions to generate nearly quantitative yields of the acids in reasonable time. The reactions are conducted under ambient conditions without any catalyst or specialized equipment. Abstract : This communication addresses very specific problem related to the synthesis of alkyl alkylphosphonic acids which are important from the verification point of view of chemical weapons convention (CWC). In contrast to the lengthy and cumbersome synthetic procedures, the reported method offers nearly quantitative yields of the acids within reasonable time.